KONSEP PERBUATAN MELAWAN HUKUM DALAM TINDAK PIDANA - TITIN APRIANI (Universitas Mahasaraswati Mataram, 2019)
The purpose of this study is to find out: (a), whether an act of crime can be said to be an act against the law. (b). what form of law is applied between an act against the law and an act of crime. This research is useful to provide knowledge in reviewing or applying a legal science specifically acts against the law, criminal law, criminal procedure law, through an empirical action in the field / society. While practically, the results of this study will be utilized as an input or contribution to the thought of officials / related officials to improve the quality of the implementation of tasks, especially in the application of applicable legal regulations for similar cases. The results of the study show that the understanding of acts against the law is more often expressed by experts. Of the many experts who formulated the notions of unlawful acts (PMH) with each other will be different, so to understand them materially we need elements to classify a particular act into PMH or not, so that the existence of these elements is expected to create an understanding of notion of acts against the law